Centro de Arte Circense do Amazonas - Pontes, Lara Céli Lima (Brasil, 2022)
The present work embraces the proposal of valuing Circus Art as a means of promoting culture, entertainment, leisure, well-being, and health to the population of Manaus, bringing recognition to the circus and not allowing its history and practices to be forgotten and/or devalued. For this reason, the design development of the Amazonas Circus Art Centre - CAC/AM was proposed with the intention of offering training in different acrobatic, artistic and dancing modalities. In addition to the areas of fashion/sewing, makeup, theater, and theoretical backstage training. Providing, in addition to leisure, training and professional training in the aforementioned areas. Research was carried out to conceptualize and define the theme, presenting case studies that guided its development, choice of terrain, environmental physical conditioning, surroundings, functional conditioning, elaboration of the Preliminary Study and as a final evaluation the development of the Preliminary Project.